2011
DOI: 10.1111/j.1600-6143.2011.03622.x
|View full text |Cite
|
Sign up to set email alerts
|

Hearts From DCD Donors Display Acceptable Biventricular Function After Heart Transplantation in Pigs

Abstract: Cardiac transplantation is in decline, in contrast to other solid organs where the number of solid organ transplants from donors after circulatory death (DCD) is increasing. Hearts from DCD donors are not currently utilized due to concerns that they may suffer irreversible cardiac injury with resultant poor graft function. Using a large animal model, we tested the hypothesis that hearts from DCD donors would be suitable for transplantation. Donor pigs were subjected to hypoxic cardiac arrest (DCD) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 20 publications
0
56
0
Order By: Relevance
“…Previous studies of myocardial recovery in large animal DCD models have exposed the heart to WITs ranging from 15 to 30 min, with varying results (2,3,26). Ali et al (3) in a porcine model demonstrated good biventricular functional recovery postorthotopic transplantation following 20.9 AE 2.8-min WIT, while Osaki et al (26) reported partial recovery of hearts subjected to 30-min WIT in a porcine transplant model using controlled initial reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of myocardial recovery in large animal DCD models have exposed the heart to WITs ranging from 15 to 30 min, with varying results (2,3,26). Ali et al (3) in a porcine model demonstrated good biventricular functional recovery postorthotopic transplantation following 20.9 AE 2.8-min WIT, while Osaki et al (26) reported partial recovery of hearts subjected to 30-min WIT in a porcine transplant model using controlled initial reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al (3) in a porcine model demonstrated good biventricular functional recovery postorthotopic transplantation following 20.9 AE 2.8-min WIT, while Osaki et al (26) reported partial recovery of hearts subjected to 30-min WIT in a porcine transplant model using controlled initial reperfusion. Similarly, Repse et al (2) also showed inferior cardiac power recovery of canine hearts subjected to 30-min WIT compared with normal control hearts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of normothermic regional perfusion, originating from Barnard's clinical work, was explored by Ali et al using a porcine model of hypoxic induced DCD (12). Following death, cardio-pulmonary bypass was established and after allowing for a period of less than hour with the heart offloaded and allowed to recover, bypass was weaned and the heart functionally assessed using load independent contractility.…”
Section: Animal Models Of Dcd Heart Donationmentioning
confidence: 99%